AKTIVITAS SITOTOKSIK PROPRANOLOL TERHADAP SEL KANKER PAYUDARA MCF7 IN VITRO (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2018)
Background: Propranolol is a nonselective beta-blocker drug which is commonly used as an antihypertensive. In vitro studies showed that propranolol has anti-proliferative, anti-migratory and cytotoxic effects on cancer cells of lung, colon, breast, nasopharynx, ovarian pancreas and gastric. Therefore, this study is conducted to assess whether propranolol has cytotoxic activity of MCF7 breast cancer cells. Research objectives: This study aimed to assess the effects of propranolol on the cytotoxic activity of MCF7 breast cancer cells. Research methods: This quasi-experimental research using post-test with a non-equivalent control group design. Cytotoxicity test using MTT assay was performed to determine the IC50 propranolol against MCF7 cells. Results: Propranolol showed cytotoxic activity against MCF7 breast cancer cells with IC50 value of 227.91 ± 14.74 µM (67,41±4,35 µg/mL). Conclusion: Propranolol has cytotoxic activity against MCF7 breast cancer cells. Keywords: propranolol, cytotoxic, MCF7